Cytokine profiles in the sera of Egyptian patients with oral pemphigus vulgaris - Hossam Eid; Basiouny El-Gamal (Universidade Estadual de Campinas, 2015)
Cytokines have been suggested to play an important role in the pathogenesis of various inflammatory and autoimmune diseases, including the potentially fatal blistering disease, oral pemphigus vulgaris (PV). No data are currently available on the cytokine levels in the sera of Egyptian patients with oral PV. Aim:The aim of this study was to measure the serum levels of some proinflammatory and antiinflammatory cytokines in Egyptian patients with PV. Methods: Using highly sensitive ELISA kits, the levels of TNF-α, IL-2, IL-4 and IL-6 were measured in the sera of 10 patients affected with oral PV and 10 healthy subjects. Results: Serum levels of TNF-α and IL-6 were found to be significantly higher in patients with oral PV than in healthy controls (p<0.001). On the other hand, no significant differences were observed in the levels of IL-2 and IL-4 between oral PV and control sera (p<0.05). Conclusions: These data showed that TNF-α and IL-6 levels were significantly increased in the sera of Egyptian patients with oral PV and this might suggest its role in the pathogenesis of this disease.